Local expenditure financing response in regencies and municipalities in Indonesia: Analysis of the flypaper effect phenomenon - Septianingrum, Nabila Ardyamita; Halim, Abdul; Utami, Tiyas Puji (Journal of Accounting and Investment, 2025)
Research aims: This research aims to analyze the flypaper effect on regencies and municipalities in Indonesia, considering the medium-term expenditure framework and their economic conditions.Design/Methodology/Approach: Quantitative methodology with secondary data from 226 regencies/municipalities in Indonesia was used. The first hypothesis testing was to find whether there was a different expenditure mean value, and if there were any, hypothesis testing about flypaper occurrence would be performed.Research findings: The results show that there was no difference in capital expenditure mean value because there was a target of capital expenditure set for every local government. Therefore, flypaper effect occurrence hypothesis testing was not performed, and there was different operational expenditure mean values. The flypaper effect did not occur in rich local governments but in poor ones.Theoretical contribution/Originality: This research fills the research gap of flypaper effect occurrence on capital expenditure and operational expenditure based on local governments’ economic conditions.Practitioner/Policy implication: This research implies that intergovernmental transfers should be used accordingly, and local governments should increase their local own-source revenue so that they wouldn’t be dependent on the transfers from the central government.Research limitation/Implication: The limitations of this study were related to the data period (abnormal condition of COVID-19) and statistical data (further explanation from primary data needed).